ANALISIS PERMASALAHAN PENDIDIKAN DI SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Muhammad Imam Syafi'i (Al-Rabwah, 2021)
The purpose of writing this article is to describe the implementation of education in elementary schools during the Covid-19 pandemic, educational problems in elementary schools during the Covid-19 pandemic, and efforts to solve educational problems in elementary schools during the Covid-19 pandemic. The method implemented is a qualitative research method with the type of literature study (Library Research). The result is that the implementation of education in elementary schools during the Covid-19 pandemic is generally carried out by utilizing various applications, namely using the Whatsapp application combined with the zoom application in learning and can also be done with a combination of the Whatsapp application and google classroom in terms of assignments. The problems of education in elementary schools during the Covid-19 pandemic include: the material delivered is not yet accessible to students, the lack of teacher ability to apply technology in learning, the lack of teacher ability to control, problems with students and digital literacy. Furthermore, efforts to solve educational problems in elementary schools during the Covid-19 pandemic are by developing two-way communication, making teachers facilitators, informants, motivators, organizers, and developing digital literacy and learning objectives.